Interview with Prof. Chou: the use of a suitable boron drug in boron neutron capture therapy will be beneficial to treat liver cancer patients - Shih, Tung-Lun (Therapeutic Radiology and Oncology, 2018)
Boron neutron capture therapy (BNCT) has a quite long history. Nevertheless, BNCT has not been a mainstream therapy for cancer treatment. Despite the fact that BNCT has not been widely known, it is a therapy which has the potential to be well-known with the further advancement of technique and cultivation of talents.